Corporate governance in the shadow of the state - Moore, Marc T. (Oxford, United Kingdom Portland, Oregon Hart Publishing, 2013)
Over recent decades corporate governance has developed an increasingly high profile in legal scholarship and practice, especially in the US and UK. But despite widespread interest, there remains considerable uncertainty about how exactly corporate governance should be defined and understood. In this important work, Marc Moore critically analyses the core dimensions of corporate governance law in these two countries, seeking to determine the fundamental nature of corporate governance as a subject of legal enquiry. In particular, Moore examines whether Anglo-American corporate governance is most appropriately understood as an aspect of 'private' (facilitative) law, or as a part of 'public' (regulatory) law. In contrast to the dominant contractarian understanding of the subject, which sees corporate governance as an institutional response to investors' market-driven private preferences, this book defines corporate governance as the manifestly public problem of securing the legitimacy - and, in turn, sustainability - of discretionary administrative power within large economic organisations. It emphasises the central importance of formal accountability norms in legitimating corporate managers' continuing possession and exercise of such power, and demonstrates the structural necessity of mandatory public regulation in this regard. In doing so it highlights the significant and conceptually irreducible role of the regulatory state in determining the key contours of the Anglo-American corporate governance framework. The normative effect is to extend the state's acceptable policy-making role in corporate governance, as an essential supplement to private ordering dynamics. Shortlisted for The Peter Birks Prize for Outstanding Legal Scholarship 2013
1: Introduction -- I. What is this Book About? -- II. The Plan for the Book -- III. Provisos to the Following Discussion -- 2: Defining Corporate Governance as a Subject of Legal Enquiry -- I. The Problem of Corporate-Managerial Power -- II. The Structural Imperative of Legitimating Corporate-Managerial Power -- III. Why Shareholder Exclusivity? -- IV. Summary -- 3: The Contractarian Paradigm of Corporate Governance Law -- I. The Purported 'Privity' of Anglo-American Corporate Law -- II. (A Brief) Historical and Intellectual Background to Corporate Contractarianism -- III. How Do Contractarians Rationalise the Most Prominent Features of Anglo-American Corporate Governance? -- IV. Legitimating Reciprocal Power Imbalance Within the Contractarian Paradigm -- V. Summary -- 4: The Contractual Dimensions of US Corporate Governance Law -- I. 'Opt-Out', 'Opt-In', and Reversible-Default Rules -- II. Competitive Federalism -- III. Judicial Deference to Private Ordering: The Business Judgment Rule -- IV. Anti-Takeover Measures -- V. Federal Deference to Private Ordering: The Rule 14a-8 Proposal -- VI. The US Corporate Board as a Pre-Regulatory Institution -- VII. Summary -- 5: The Contractual Dimensions of UK Corporate Governance Law -- I. The Contractual Principle -- II. Judicial Deference to Private Ordering -- III. The Endogeneity of the British Corporate Board -- IV. Market-Invoking Regulation -- V. Summary -- 6: The (Expanding) Regulatory Dimensions of Anglo-American Corporate Governance Law -- I. The 'De-Privatisation' of Anglo-American Corporate Governance Law? -- II. The Mandatory Nature of Corporate Disclosure Regulation in the United States and United Kingdom -- III. The Regulatory Division of Corporate Decision-Making Power in the UK -- IV. The Counter-Contractual Nature of the Equitable Fiduciary Principle under Anglo-American Law -- V. Summary -- 7: Rationalising Regulatory State Paternalism within an Expanded Contractarian Paradigm -- I. Are Mandatory Rules 'Mandatory' at all? -- II. The Acceptable Ambit of State Interventionism in Private Ordering: Negative Externalities and Public Goods -- III. The 'Market Mimicking' Rationalisation of Regulatory State Interventionism -- IV. The Limitations of the 'Market Mimicking' Rationalisation -- V. Expanding the Frontiers of the Contractarian Paradigm -- VI. Summary -- 8: Conclusions
Includes bibliographical references (pages 283-294) and index
Also issued in print
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Electronic reproduction.
Keywords: Corporate governance -- Law and legislation -- Great Britain; Corporate governance -- Law and legislation -- United States